ANALISIS PENGGUNAAN FRAMEWORK WEBSITE JDIH KHUSUS PERATURAN KEMENTERIAN REPUBLIK INDONESIA - Yahya Noviko Rahman; Rizal Maulana Hadi; Mursyidatun Nabilah; Muhammad Hanif Waskito; Nur Aini Rakhmawati (Universitas Islam Kuantan Singingi, 2020)
The development of website technology is currently very rapidly developing. In general, the use of websites in government agencies is not new and has become common in government agencies, one of which is in the realm of the ministry. The website is used for various purposes, ranging from information for the public to operational activities. Website about Jaringan Dokumentasi dan Informasi Hukum (JDIH) is a form of implementation of regulations that state that all things about law are public information, so the public must be able to access information related to legal products from the ministry. For this reason, we are trying to identify the framework of each Ministry’s JDIH website using Wappalyzer to analyze how the website distributes its legal products in terms of appearance and features. From this analysis, there is no standardization used on the Ministry's JDIH website.